Predictors of homework engagement in internet-delivered Parent-Child Interaction Therapy for children with developmental delay: what about acculturation and enculturation? - Cafatti Mac-Niven, Anastassia; Comer, Jonathan S.; Bagner, Daniel M. (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionFamilies from racial/ethnic minoritized backgrounds and families of children with developmental delay (DD) often face more obstacles to engaging in psychosocial interventions compared to White families and families of typically developing children. Yet, research on engagement in behavioral parenting interventions has predominantly focused on typically developing children and White families from majority cultural groups. The present study offers the first examination of acculturation and enculturation as predictors of homework engagement among caregivers of children with DD from underrepresented racial/ethnic backgrounds participating in a telehealth behavioral parenting intervention.MethodsData were collected from 65 caregiver-child dyads participating in the Advancing Child Competencies by Extending Supported Services (ACCESS) Study evaluating Internet-delivered Parent-Child Interaction Therapy (iPCIT) for children with DD. Homework engagement was measured as the proportion of days caregivers practiced “special time” with their child. Acculturation and enculturation were assessed using the Abbreviated Multidimensional Acculturation Scale (AMAS). Linear regression analyses evaluated associations between these two cultural factors and subsequent homework engagement, controlling for caregiver nativity, language of preference, income-to-needs ratio (INR), and caregiver work status.ResultsWhile higher levels of acculturation (B = .110, p = .054) did not significantly predict homework engagement, enculturation (B = .140, p = .007) significantly predicted greater homework engagement throughout treatment with small and small-to-medium effect sizes (Cohen's f² = 0.029 and 0.104, respectively).DiscussionThese findings underscore the nuanced role of acculturation and enculturation in predicting homework engagement in telehealth behavioral interventions for children with DD. Although acculturation did not facilitate homework engagement, caregivers who retained a stronger connection to their cultural heritage demonstrated higher homework engagement within the context of iPCIT. The study highlights the need for incorporating cultural considerations into treatment planning and flexibility in adapting treatment protocols to optimize family engagement and improve outcomes in this population.Clinical Trial RegistrationClinicalTrials.gov, identifier (NCT03260816).